2020
DOI: 10.1080/20477724.2020.1826152
|View full text |Cite
|
Sign up to set email alerts
|

Late incidence of SARS-CoV-2 infection in a highly-endemic remote rural village. A prospective population-based cohort study

Abstract: Data on SARS-CoV-2 transmission in rural communities is scarce or non-existent. A previous cross-sectional study in middle-aged and older adults enrolled in the Atahualpa Project Cohort demonstrated that 45% of participants had SARS-CoV-2 antibodies, 77% of whom were symptomatic. Here, we assessed the incidence of SARS-CoV-2 infection in the abovementioned rural population. One month after baseline testing, 362 of 370 initially seronegative individuals were re-tested to assess incidence of seroconversion and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…As such, we may have missed cases of HGS decline among middle-aged adults with SARS-CoV-2 infection. In addition, although the lateral flow-based antibody test we used is reported to have high diagnostic reliability, we cannot exclude the possibility of some degree of misclassification due to false positive or false negative results, 16,17 or the improbable scenario of cross-reactions with other viruses that are endemic in the region. 46 In summary, this longitudinal study cohort demonstrated in a select cohort an independent detrimental association between SARS-CoV-2 and HGS worsening, which reached significance among individuals with older rather than more recent infections.…”
Section: Discussionmentioning
confidence: 99%
“…As such, we may have missed cases of HGS decline among middle-aged adults with SARS-CoV-2 infection. In addition, although the lateral flow-based antibody test we used is reported to have high diagnostic reliability, we cannot exclude the possibility of some degree of misclassification due to false positive or false negative results, 16,17 or the improbable scenario of cross-reactions with other viruses that are endemic in the region. 46 In summary, this longitudinal study cohort demonstrated in a select cohort an independent detrimental association between SARS-CoV-2 and HGS worsening, which reached significance among individuals with older rather than more recent infections.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional and longitudinal epidemiological studies on SARS-CoV-2 infection have been conducted in this village. [15][16][17][18][19] As previously reported, Atahualpa's residents are homogeneous regarding race/ethnicity (Amerindian ancestry), socio-economic status (most men belong to the blue collar class and work as artisan carpenters, and most women are homemakers), and dietary habits (the diet is ancestrally rich in oily fish, vegetables, fruits, and carbohydrates but poor in other types of meat and dairy products). People get food mostly from the fish market and small grocery stores where highly processed foods are rarely found.…”
Section: Study Populationmentioning
confidence: 99%
“…Since its inception the adult population of Atahualpa has undergone tests for assessing cognitive performance, cerebrovascular diseases, epilepsy, sleep disorders and other conditions of interest [18][19][20][21]. Atahualpa was severely struck by the SARS-CoV-2 pandemic, as evidenced by a mortality rate of 21.6 per 1000 population during March-April 2020 [22], a seroprevalence of 45% among survivors [23] and an incidence rate ratio of 7.4 per 100 person-months of potential virus exposure [24]. Taking the unique opportunity of the well-established Atahualpa Project cohort, the present longitudinal prospective study aimed to assess the occurrence of cognitive decline 6 months after an episode of mild symptomatic SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%